Effect of an argon matrix on the vibrational spectra of trapped water clusters - Vasylieva, A.O.; Doroshenko, I.Yu.; Pogorelov, V.E.; Bulavin, L.A. (Reports of the National Academy of Sciences of Ukraine, 2018)
Quantum-chemical calculations of infrared absorption spectra for different sized water clusters in different solvations are performed using the software Gaussian 03. The influence of the argon medium on the vibrational spectra of water clusters isolated in the argon matrix is determined, by comparing the obtained values of frequencies and intensities of spectral bands in water and argon solvations.